3
$\begingroup$

I was revising some differentiation, when I observed something that I pretty much always took for granted, so I decided to write it in mathematical notation. Would you please tell me if I'm correct to say the following:

If $f(X) = cg(X)$, $c$ is a constant then $f'(X) = cg'(x)$.

Where $f'(x)$ and $g'(x)$ means 'gradient of each function'.

$\endgroup$
  • 3
    $\begingroup$ Yes, that's correct. $\endgroup$ – Cookie Mar 27 '15 at 22:25
  • 4
    $\begingroup$ This follows directly from the definition: $f'(x) = \lim_{h\to 0}\frac{f(x+h)-f(x)}{h} = \lim_{h\to 0}\frac{cg(x+h)-cg(x)}{h} = c\lim_{h\to 0}\frac{g(x+h)-g(x)}{h} = cg'(x)$ using the fact that a constant factor commutes with the limit. $\endgroup$ – Winther Mar 27 '15 at 22:37
  • 1
    $\begingroup$ @Winther: Post your comment as an answer...? :) $\endgroup$ – Andrew D. Hwang Mar 27 '15 at 23:00
1
$\begingroup$

This follows directly from the definition:

$f'(x) = \lim_{h\to 0}\frac{f(x+h)-f(x)}{h} = \lim_{h\to 0}\frac{cg(x+h)-cg(x)}{h} = c\lim_{h\to 0}\frac{g(x+h)-g(x)}{h} = cg'(x)$

using the fact that a constant factor commutes with the limit.

$\endgroup$
0
$\begingroup$

That usually one of the first theorems you learn about the derivative (right after 'the derivative of a constant function is 0').

$\endgroup$
0
$\begingroup$

You are correct.

let us have $h(x)=c$

$f(x)=c\cdot g(x)=h(x)\cdot g(x)$

Now using the product rule.

$f'(x)=h'(x)\cdot g(x)+g'(x)\cdot h(x)=0\cdot g(x) + g'(x)\cdot c=c\cdot g(x)$

Note that the derivative of a constant is zero.

$\endgroup$
  • $\begingroup$ I think for this proof you shouldn't use the product rule, meaning that this result is known before the product rule is introduced. $\endgroup$ – Hirshy Aug 24 '15 at 6:21

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.